2017
DOI: 10.1186/s40425-017-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

The immune system in cancer metastasis: friend or foe?

Abstract: Metastatic disease is the leading cause of death among cancer patients and involves a complex and inefficient process. Every step of the metastatic process can be rate limiting and is influenced by non-malignant host cells interacting with the tumor cell. Over a century ago, experiments first indicated a link between the immune system and metastasis. This phenomenon, called concomitant immunity, indicates that the primary tumor induces an immune response, which may not be sufficient to destroy the primary tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
196
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(199 citation statements)
references
References 126 publications
2
196
0
1
Order By: Relevance
“…It is unclear how the complex interplay between tumor cells and the tumor microenvironment (TME) and their interactions affect treatment outcome in metastatic cancer (Kitamura, Qian, and Pollard 2015;Janssen et al 2017;Robinson et al 2017). Investigating this interplay in an advanced disease setting is complicated by the difficulty of obtaining multiple-site tumor samples and the finding that different tumors within the same individual can harbor 30 distinct immune microenvironments (Sridharan et al 2016;Jiménez-Sánchez et al 2017a;Reuben et al 2017;A.…”
Section: Introduction 25mentioning
confidence: 99%
“…It is unclear how the complex interplay between tumor cells and the tumor microenvironment (TME) and their interactions affect treatment outcome in metastatic cancer (Kitamura, Qian, and Pollard 2015;Janssen et al 2017;Robinson et al 2017). Investigating this interplay in an advanced disease setting is complicated by the difficulty of obtaining multiple-site tumor samples and the finding that different tumors within the same individual can harbor 30 distinct immune microenvironments (Sridharan et al 2016;Jiménez-Sánchez et al 2017a;Reuben et al 2017;A.…”
Section: Introduction 25mentioning
confidence: 99%
“…An ability to escape the immune response is important for cancer cells to survive in circulation and form metastasis in distant organs (Janssen et al, 2017;Blomberg et al, 2018). In our previous study, we found that AGC1-KD cells have lower cytosolic NAD + /NADH ratio and are less glycolytic (Alkan et al, 2018).…”
Section: Genes Related To Aldh1l1 Metabolism Are Deregulated In Agc1-mentioning
confidence: 93%
“…TGFß1 expression is increased in the tumor epithelial cells of Smad4 −/− SCCs, and TGFß1 overexpression was associated with increased infiltration of granulocytes, macrophages, T cells, and Th17 cells in the tumor microenvironment . Tumor‐associated granulocytes, macrophages, and regulatory T cells (Tregs) can each block CD8+ T cell infiltration to promote tumor progression . Tregs can also block functional CD8+ and NK cells from attacking circulating metastatic cancer cells .…”
Section: Tumor Microenvironment and Progression Of Smad4 Deficient Sccsmentioning
confidence: 99%
“…6 Tumor-associated granulocytes, macrophages, and regulatory T cells (Tregs) can each block CD8+ T cell infiltration to promote tumor progression. 53,54 Tregs can also block functional CD8+ and NK cells from attacking circulating metastatic cancer cells. 53 Th17 cells play a controversial role in tumor immunity to either suppress or promote tumor progression depending on the malignancy.…”
Section: F I G U R E 1 Normal Versus Deficient Smad4 Signaling a Smad4mentioning
confidence: 99%
See 1 more Smart Citation